Chrysis bidentata subsp. prominea Linsenmaier 1959 - Rosa, Paolo; Greeff, Michael (Zenodo, 2021)
Chrysis bidentata prominea Linsenmaier, 1959 Chrysis ( Chrysis ) bidentata ssp. prominea Linsenmaier, 1959: 131. Holotype ♀; Switzerland: Wallis (NMLU). Chrysis ( Chrysis ) consanguinea prominea : Linsenmaier 1997: 277 (key). Type locality. France, Italy, Switzerland: “ Süd-Frankreich, Sizilien, Schweiz (Wallis). Selten. ♀ Type, ♁ Allotype (Wallis 500-900m, VII.) Coll. m., Paratypen Coll. Verhoeff und Coll. m. ”. Paratypes, 3♀♀: France Vaucl. Carpentras 30.v.59 Linsenmaier // Paratypen <handwritten in red> Chrysis L. bidentata Luc. prominea Lins . Linsenmaier det. 59 // PARATYPUS <red label>. Remarks. Three paratype specimens are prepared and glued on the same plastic label, in Linsenmaier’s typical style (Rosa et al. 2015b). They were given in exchange by Linsenmaier, after examination of Nadig’s collection in 1963, together with other paratypes (see below) and interesting specimens. Linsenmaier (1959, 1968, 1987) confused the name Elampus bidentatus Lucas, 1849 (a northern African species belonging to the tribe Elampini) with Chrysis bidentata Linnaeus, 1767 (described from Sweden and belonging to the tribe Chrysidini, Chrysis viridula group), which is a junior synonymous of Chrysis viridula Linnaeus, 1761 (Paukkunen et al. 2014). Chrysis bidentata Lucas, 1849 sensu Linsenmaier (1959, 1968, 1987) is Chrysis consanguinea Mocsáry, 1889 (described from Algeria). Linsenmaier (1997, 1999) recognized his misinterpretation; however, this inaccuracy is still found in recent articles (e.g. Tarbinsky 2002). : Published as part of Rosa, Paolo & Greeff, Michael, 2021, Types of Chrysididae (Insecta, Hymenoptera) deposited at the Eidgenössische Technische Hochschule in Zürich, pp. 181-204 in Zootaxa 4908 (2) on page 183, DOI: 10.11646/zootaxa.4908.2.2, http://zenodo.org/record/4438229 : {"references": ["Linsenmaier, W. (1959) Revision der Familie Chrysididae (Hymenoptera) mit besonderer Berucksichtigung der europaischen Spezies. Mitteilungen der Schweizerischen Entomologischen Gesellschaft, 32 (1), 1 - 232.", "Linsenmaier, W. (1997) Altes und Neues von den Chrysididen. (Hymenoptera, Chrysididae). Entomofauna, 18 (19), 245 - 300.", "Rosa, P., Bernasconi, M. V. & Wyniger, D. (2015 b) The Linsenmaier Chrysididae collection housed in the Natur-Museum Luzern (Switzerland) and the main results of the related GBIF Hymenoptera Project (Insecta). Zootaxa, 3986 (5), 501 - 548. https: // doi. org / 10.11646 / zootaxa. 3986.5.1", "Linsenmaier, W. (1968) Revision der Familie Chrysididae (Hymenoptera). Zweiter Nachtrag. Mitteilungen der Schweizerischen Entomologischen Gesellschaft, 41 (1 - 4), 1 - 144.", "Linsenmaier, W. (1987) Revision der Familie Chrysididae. (Hymenoptera). 4 Teil. Mitteilungen der Schweizerischen Entomologischen Gesellschaft, 60 (1 - 2), 133 - 158.", "Lucas, H. (1849) Les Chrysidiens. In: Exploration scientifique de l'Algerie. Zoologie. Histoire naturelle des animaux articules, 3, 304 - 316.", "Linnaeus, C. (1767) Systema Naturae per Regna Tria Naturae, secundum Classes, Ordines, Genera, Species, cum characteribus, differentiis, synonymis, locis. Editio Duodecima, Reformata. Tom I. Pars II. Impensis direct. Laurentii Salvii, Holmiae, 775 pp. [pp. 553 - 1327] https: // doi. org / 10.5962 / bhl. title. 68927", "Linnaeus, C. (1761) Fauna Svecica sistens Animalia Sveciae Regni: Mammalia, Aves, Amphibia, Pisces, Insecta, Vermes. Distributa per Classes et Ordines, Genera et Species, cum Differentiis, Specierum, Synonymis, Auctorum, Nominibus Incolarum, Locis natalium, Descriptionibus Insectorum. Editio Altera, Auctior. Laurentius Salvius, Stockholmiae, 578 pp., 2 pls. https: // doi. org / 10.5962 / bhl. title. 46380", "Paukkunen, J., Rosa, P., Soon, V., Johansson N. & Odegaard, F. (2014) Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae). Zootaxa, 3864 (1), 1 - 67. https: // doi. org / 10.11646 / zootaxa. 3864.1.1", "Mocsary, A. (1889) Monographia Chrysididarum Orbis Terrarum Universi. Hungarian Academy of Science, Typis Societatis Franklinianae, Budapest, 643 pp.", "Linsenmaier, W. (1999) Die Goldwespen Nordafrikas (Hymenoptera, Chrysididae). Entomofauna, Suppl. 10, 1 - 281.", "Tarbinsky, Yu. S. (2002) [The golden wasp genus Chrysis L. (Hymenoptera, Chrysididae) in Tien Shan and adjacent territories. IV. Species groups graelsii, comparata, splendidula, viridula, scutellaris]. [Entomological Investigations in Kyrgyzstan], 22, 31 - 44. [in Russian with English summary]"]}